Understanding Abstract Wonderment - Damian Stoupe (Grounded Theory Review: An International Journal)
The aim of this paper is to present a novice researcher’s understanding of Glaser’s dictum to approach classical grounded theory studies with a sense of abstract wonderment. In the paper, the argument is made that far from being a preposterous concept, cultivating abstract wonderment as a form of praxis can help liberate the researcher from the bonds of preconceptions and attachments, which impede the emergence of a grounded theory. The paper reflects a personal grounded theory study arising after a crisis of confidence encountered during a formal PhD grounded theory study. It offers considerations on how to cultivate a sense of awe and abstract wonderment.